Angiotensin II mediates catecholamine and neuropeptide Y secretion in human adrenal chromaffin cells through the AT1 receptor - Cavadas, Cláudia (2003)
The aim of the present work was to study the effect of angiotensin II (Ang II) on catecholamines and neuropeptide Y (NPY) release in primary cultures of human adrenal chromaffin cells. Ang II stimulates norepinephrine (NE), epinephrine (EP) and NPY release from perifused chromaffin cells by 3-, 2- and 12-fold, respectively. The NPY release is more sustained than that of catecholamines. We found that the receptor-AT2 agonist, T2-(Ang II 4-8)2 has no effect on NE, EP and NPY release from chromaffin cells. We further showed that Ang II increases intracellular Ca2+ concentration ([Ca2+]i). The selective AT1-receptor antagonist Candesartan blocked [Ca2+]i increase by Ang II, while T2-(Ang II 4-8)2 was ineffective. These findings demonstrate that AT1 stimulation induces catecholamine secretion from human adrenal chromaffin cells probably by raising cytosolic calcium.